Evidencing enhanced oxygen and hydrogen evolution reactions using In–Zn–Co ternary transition metal oxide nanostructures: A novel bifunctional electrocatalyst. (30th August 2019) - Ilanchezhiyan, P.; Kumar, G. Mohan; Siva, C.; Madhankumar, A.; Jeon, H.C.; Kang, T.W.; Kim, D.Y.
Abstract: Ternary transition metal oxides are gaining popularity for cost effective bifunctional electrocatalytic activities and to realization of novel water splitting devices. In this regard, In2 O3 /ZnO/Co3 O4 based ternary oxide nanostructures were investigated in detail for their oxygen/hydrogen evolution reaction (OER/HER) in alkaline environment. The ternary oxides were at first processed through a simple chemical route involving hydrothermal treatment. The prepared nanostructures were then investigated by using high-resolution transmission electron microscopy (TEM/HRTEM) to ascertain their morphological traits. X-ray diffraction, Raman signals and photoluminescence data demonstrated the In2 O3 phase to be prevalent in the ternary mixture on par with that of ZnO and Co3 O4 . The valence state of various metal ions and the In–O, Zn–O and Co–O bonding was verified using XPS. The ternary oxide coated electrodes exhibited excellent overall water splitting activity. Overpotential values of 398 and 510 mV were registered for OER and HER experiments under a current density of ±10 mA cm −2, demonstrating the material to be an ideal OER/HER electrocatalyst at room temperature. The exceptional long-term stability in ternary oxides and their Tafel slope (88 mV/dec for OER and 60 mV/dec for HER) further affirmed their unique anodic/cathodic characteristics for water splitting applications. Highlights: Indium-zinc-cobalt based ternary oxides were processed via hydrothermal technique. The oxides offered enriched surface area for effective charge transfer. Ternary oxides exhibit excellent OER/HER activity with Tafel values 88 and 60 mV/dec. Long-term durability of electrocatalyst for OER/HER was affirmed.